GRAFTING PRODUCT OF MALEIC ANHYDRIDE ONTO CYCLIZED NATURAL RUBBER IN AN INTERNAL MIXER: PHYSICAL PROPERTIES AND COMPATIBLITY WITH POLYAMIDE - M. Said Siregar (AGRIUM: Jurnal Ilmu Pertanian, 2015)
The research of grafting Maleic Anhydride onto Cyclized Natural Rubber has been carried out in an Internal Mixer 150oC in absence of Benzoyil Peroxide with rotor speed 80 rpm. Physical properties of the grafting product determined such as softening point, acid value, color, viscosity, and glass transition themperature. Compatibilty of the grafting product also investigated. The physical properties of the grafting product were not signicanly different with blank, except glass transition themperature was increased. Compatiblity of grafting product with polyamide was increased.Keywords: grafting, cyclic natural rubber, maleic anhydride, physical properties, compatiblity